2010
DOI: 10.1002/hyp.7598
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the impact of rural land management changes on catchment runoff generation in England and Wales

Abstract: Abstract:Although reviews of the scientific literature have failed to demonstrate conclusive evidence for the impact of rural land management on peak runoff rates, increasing emphasis is being placed by policy makers on its role in catchment-scale flood risk management. Poor soil and field conditions can lead to higher rates of runoff from extreme rainfall events; however, the improvement of land condition will lead to differing runoff responses depending on land use, soil type and climatic regime. This study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 32 publications
1
41
0
Order By: Relevance
“…Soils with BFI Ã HOST close to the cutoffs are classified as either of two USDA classes, e.g., HOST type 15 is classified as the USDA soil type C or D. Although this mapping contains significant uncertainty, it is presumed to be useful in that it provides information about land use and management effects that would otherwise not be available for UK applications. The proposed HOST to USDA soil group mapping is similar to the mapping hypothesized by Hess et al [2010].…”
Section: Regionalized Indices As Sources Of Informationmentioning
confidence: 62%
“…Soils with BFI Ã HOST close to the cutoffs are classified as either of two USDA classes, e.g., HOST type 15 is classified as the USDA soil type C or D. Although this mapping contains significant uncertainty, it is presumed to be useful in that it provides information about land use and management effects that would otherwise not be available for UK applications. The proposed HOST to USDA soil group mapping is similar to the mapping hypothesized by Hess et al [2010].…”
Section: Regionalized Indices As Sources Of Informationmentioning
confidence: 62%
“…There are many overlapping and related ways in which both environmental management and flood risk are framed, with related uncertainties. For example natural flood management (NFM) is sometimes characterised as uncertain because it lacks a 'sufficient' scientific evidence base (O'Connell et al 2007;Marshall et al 2009;Hess et al 2010). The majority of scientific analyses of NFM explore the question of whether upland land management can affect river flow in order to attenuate flood peaks (Lane et al 2006;McCormick et al 2009).…”
Section: Approaches To Flood Risk Management (Frm)mentioning
confidence: 99%
“…Although originally developed as a teaching and learning tool [16], its value in hydrological research has been demonstrated in several applications including estimation of irrigation requirements [17], runoff estimation [18], drainage performance [19] and groundwater recharge potential [20]. Full details of the modelling approach are given in Hess et al [21].…”
Section: Wasim Daily Water Balance Methodsmentioning
confidence: 99%